Use of sildenafil in a patient with pulmonary hypertension: A case report (Research, Society and Development, 2021)
The aim of this study is to report a case of a patient with chronic obstructive pulmonary disease (COPD) and cystic fibrosis that evolved with pulmonary hypertension, reporting the clinical findings and the treatment instituted. Patients who have a chronic lung disease are more likely to develop pulmonary hypertension, a condition that leads to increased levels of pulmonary vascularization, a condition that leads to reduced carrier survival. The diagnosis of this condition can take up to 2 years, since most of the symptoms are nonspecific, in addition to the requirement for invasive methods to confirm the diagnosis. The patient in the clinical case showed signs suggestive of pulmonary hypertension, in addition to a chest X-ray consistent with the findings of this pathology, so treatment with a vasodilator was started. The vasodilator of choice was sildenafil because it is an agent that causes apparent benefits for the patient, without major repercussions on other body systems.